The effect of compensation and work motivation on employee loyalty at Harbour BrightShoes - Ariz Rukmana, Dandi; Prasetyo, Davieri Elcid; Ginting, Hawila Natalio; Payu, Rian Maulana Hasby; Wibisono, Sony; Sofyandi, Herman (Technium Social Sciences Journal, 2022)
Human resources play an important role in the company as they exist. Loyalty in companies could increase when theycould be able to build it themselves in their environment.Companies must conduct several approaches, such as providing appropriate compensation, motivation, and a convenient work environment. Companies engaged in services such as shoe laundry need some supporting factors to attract consumers to be interested in using the services that isoffered by the company. Service quality is the main supporting factor for companies engaged in services where good service quality will certainly help companies to increase their customers. This study aims to determine the effect of compensation and work motivation on employee loyalty of Harbour Brightshoes and to obtain the results of an analysis of how much compensation affects employee loyalty of HarbourBrightshoes.